Helicobacter pylori Infection and Hepatobiliary Pathology - S. V. German; I. P. Bobrovnitsky (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim.  The aim of this review is to analyze and systematize data on the effect of Helicobacter pylori infection on hepatobiliary diseases.Background.  Over the past two decades, a growing number of studies have been devoted to the possible involvement of H. pylori infection in the extragastric pathology. The presence of the bacterium was detected in many organs and tissues. Its relationship with the development of idiopathic iron-deficiency anemia, B12 deficiency anemia, idiopathic thrombocytopenic purpura is proved. The possible role of the bacterium in the development of hepatobiliary pathology is also discussed. The presence of the bacterium has been revealed in samples taken from the liver tissue, biliary tract, bile and gallstones of patients suffering from hepatobiliary diseases. The involvement of H. pylori in the formation of gallstones is considered possible. Non-alcoholic fatty liver disease (NAFLD) is more often diagnosed in H. pylori infected individuals compared to those not infected. The progression of inflammation in the liver of any nature is noted in the presence of H. pylori infection. Different species of the Helicobacter genus, including H. pylori, are shown to contribute to the development of liver cancer. However, some researchers report data against the involvement of H. pylori in the pathogenesis of various hepatobiliary diseases.Conclusion.  The results obtained by the authors cannot be considered unambiguous, thus requiring further research. Given the high prevalence of H. pylori infection and the significant incidence of hepatobiliary pathology, the confirmation of their relationship can be of great epidemiological, preventive and clinical importance.